Epigenetic Silencing of IRF7 and/or IRF5 in Lung Cancer Cells Leads to Increased Sensitivity to Oncolytic Viruses - Li, Qunfang; Tainsky, Michael A. (PLOS ONE, 2011)
Defective IFN signaling results in loss of innate immunity and sensitizes cells to enhanced cytolytic killing after Vesticular Stomatitis Virus (VSV) infection. Examination of the innate immunity status of normal human bronchial epithelial cells Beas2B and 7 lung cancer cells revealed that the abrogation of IFN signaling in cancer cells is associated with greater sensitivity to VSV infection. The disruption of the IFN pathway in lung cancer cell lines and primary tumor tissues is caused by epigenetic silencing of critical interferon responsive transcription factors IRF7 and/or IRF5. Although 5-aza-2′-deoxycytidine treatment fails to reactivate IRF7 and IRF5 expression or protect cells from VSV infection, manipulating IFN signaling by altering IRF expression changes the viral susceptibility of these cells. Lung cancer cells can be partially protected from viral killing using IRF5+IRF7 overexpression, whereas IFN pathway disruption by transfection of siRNAs to IRF5+IRF7 increases cells' vulnerability to viral infection. Therefore, IRF5 and IRF7 are key transcription factors in IFN pathway that determine viral sensitivity of lung cancer cells; the epigenetically impaired IFN pathway in lung cancer tissues provides potential biomarkers for successful selective killing of cancer cells by oncolytic viral therapy.